The quick-reference guide to addictions and recovery counseling : 40 topics, spiritual insights, and easy-to-use action steps - Clinton, Timothy E., 1960- (Grand Rapids : Baker Books, 2013)
"We live in an addictive age, and many people are suffering silently. For anyone who is called to counsel those with addictions, The Quick-Reference Guide to Addictions and Recovery Counseling will be a welcome guide to bring hope, life, and freedom. This A-Z guide gives pastors, professional counselors, and lay helpers the information they need to help recovering church members, clients, and friends work through the spiritual and emotional issues connected to addiction. The many types of substance abuse and behavioral addictions addressed include: alcohol; caffeine; depressants; narcotics; prescription drugs; cutting and self-harm; eating disorders; gambling; hoarding; internet use and gaming; shopping; social networking. Each of the forty topics covered follows a helpful eight-part outline and identifies typical symptoms and patterns, definitions and key thoughts, questions to ask, directions for the conversation, action steps, biblical insights, prayer starters, and recommended resources"--Publisher description.
Part 1. Addictions and recovery overview. Disease and choice -- Trauma and comorbidity -- Treatment protocols -- Spiritual applications -- Recovery and relapse prevention -- Part 2. Substance abuse addictions. Alcohol -- Caffeine -- Cocaine and crack cocaine -- Depressants -- Diuretics and weight loss -- Hallucinogens -- Inhalants -- Marijuana and hashish -- Narcotics and opiates -- Nicotine -- Prescription drugs -- Stimulants -- Part 3. Behavioral addictions. Bodybuilding and body image -- Cutting and self-harm -- Eating disorders -- Fetishes and bizarre interests -- Food addictions -- Gambling -- Hoarding -- Internet use and gaming -- Kleptomania and stealing -- Pornography and sexual addiction -- Shopping and excessive collecting -- Technology and social networking -- Voyeurism and exhibitionism -- Part 4. Process addictions. Adrenaline and thrill seeking -- Anger and rage -- Anxiety and worry -- Chronic stress and self-imposed pressure -- Co-dependency and toxic relationships -- Cults and the occult -- Narcissism and attention seeking -- Obsessions and compulsions -- Religious addiction and toxic faith -- Workaholism and performance.
Includes bibliographical references (pages 356-365) and index.
Keywords: Drug abuse counseling -- Handbooks, manuals, etc; Substance abuse -- Handbooks, manuals, etc; Recovering addicts -- Handbooks, manuals, etc